STUDY OF THE THERMOMECHANICAL BEHAVIOR OF COMPACTED EARTH CONTAINING FIBERS FOR ITS USE AS CONSTRUCTION MATERIAL - Yacine LABIAD; ENCA/Miloud BEDDAR (MOHAMED BOUDIAF UNIVERSITY - M'SILA, 2025)
Recent studies have increasingly focused on incorporating sustainable materials into construction. This research examines the impact of sisal or Alfa fibers on the thermomechanical behavior of compacted earth block (CEB) utilizing local resources, specifically red clayey soil from the Msila region (East of Algeria), blended with brick waste (BW). In this study, the plasticity criteria are maintained at the maximum BW of 20%. Later, the effects of fiber and cement incorporation on CEB engineering properties, comparing different compositions, are evaluated. Sisal and Alfa fibers are introduced at proportions ranging between 0 to 0.5%, with cement added at 0%, 5%, 7%, and 9% for Sisal fibers, while for Alfa fibers-reinforced soil, cement is fixed at 7 %, all based on the weight of the modified soil. Serial tests on properties such as density, capillary absorption rate, thermal conductivity, abrasion, tensile and compressive strengths at wet and dry states are performed. The findings indicate that incorporating Sisal or Alfa fibers reduces the weight of CEB, with a 0.5% fiber content leading to a density decrease of 5.7% and 3.5%, respectively. However, this also increases capillary absorption and reduces water resistance, though cement stabilization helps mitigate these effects. Fiber incorporation improves thermal insulation, lowering thermal conductivity by up to 21% for Sisal fibers and 13% for Alfa fibers. Furthermore, compressive strength increases significantly, reaching 150% for Sisal fiber-reinforced CEB at 0.5%, while in cement-stabilized CEB, strength peaks at 0.2% before declining. Similarly, Alfa fiber incorporation enhances compressive strength with a 111.25% increase at 0.5%. Tensile strength consistently improves with increasing cement and fiber content, whereas abrasion resistance decreases at higher fiber content. Also, the study reveals that fibers alone do not provide sufficient stability for CEB in humid conditions, as the blocks lose their strength completely upon water exposure. This underscores the importance of proper water protection or cement stabilization to enhance durability. Finally, this research confirms that Sisal or Alfa fibers are a viable reinforcement material for CEB, while introducing an environmentally friendly solution for brick waste (BW) management recovery. Incorporating BW into CEB production promotes sustainable construction practices, supporting eco-conscious development and resource-efficient building strategies.
Keywords: Fibers; Compressed earth block (CEB); Thermal conductivity; Brick waste (BW); Strength; durability